Correction to: EANM enabling guide: how to improve the accessibility of clinical dosimetry - Jonathan Gear; Caroline Stokke; Christelle Terwinghe; Silvano Gnesin; Mattias Sandström; Johannes Tran‑Gia; Marta Cremonesi; Francesco Cicone; Fredrik Verburg; Roland Hustinx; Luca Giovanella; Ken Herrmann; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2023)
A correction to this paper has been published: https://doi.org/10.1007/s00259-023-06226-z .